2012
DOI: 10.1111/j.1445-5994.2012.02820.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of food allergy in Taiwan: a questionnaire‐based survey

Abstract: Less than 10% of the Taiwan population suffers from food allergy with different allergic symptoms to variable food allergens in different age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 29 publications
(61 reference statements)
8
69
1
3
Order By: Relevance
“…Singapore are comparable to those among children younger than three years old in Taiwan (0.36% based on history and skin prick test), (21) and 2-7-year-olds in Hong Kong (0.41% based on history alone). (22) Not only are the rates of egg and cow's milk allergy in Singapore low on a global scale, but it is also suspected that these food allergies are milder (less anaphylaxis) and possibly get outgrown faster (50% and 80% of children by three years of age for egg and cow's milk allergy, respectively) than in the West.…”
Section: Egg and Cow's Milkmentioning
confidence: 57%
See 1 more Smart Citation
“…Singapore are comparable to those among children younger than three years old in Taiwan (0.36% based on history and skin prick test), (21) and 2-7-year-olds in Hong Kong (0.41% based on history alone). (22) Not only are the rates of egg and cow's milk allergy in Singapore low on a global scale, but it is also suspected that these food allergies are milder (less anaphylaxis) and possibly get outgrown faster (50% and 80% of children by three years of age for egg and cow's milk allergy, respectively) than in the West.…”
Section: Egg and Cow's Milkmentioning
confidence: 57%
“…(21) The prevalence in a Hong Kong cohort of 2-7-year-olds was 0.25% (doctor diagnosed), (22) while that in China was 0.17%-0.21% among 0-2-year-olds (challenge proven). (8) However, variance in the population age and methodology makes it difficult to compare the different studies.…”
Section: Fishmentioning
confidence: 97%
“…Approximately 77% out from the 30018 food allergy sufferers surveyed by the researchers re-experienced the occurrence of food allergy incident (Wu et al, 2012). Furthermore, as estimated by Pawankar et, al (2011) for about 10-15% children in Malaysia having food allergies.…”
Section: Food Allergy Populationmentioning
confidence: 96%
“…The food allergy sufferer and their parents are struggling to survive but if the public just ignored it, the incidents of food allergy will occur. The food allergy sufferer will re -experienced the food allergy reactions as reported by Wu et al, ( 2012) if the public just ignored about the food allergy issue. As a result, the food allergy sufferer and parents will face tremendous challenges and they also have to bare the medical cost, trauma, demoralized and the quality of life is dwindle (Gaspar-Marques et al, 2014).…”
Section: Journal Of Management Researchmentioning
confidence: 99%
“…Some of the most common food allergens are highly prevalent in the USA such as fish, eggs, milk, peanuts, shellfish, soy, tree nuts, and wheat (Boyce et al 2010;Branum and Lukacs 2009), whilst sesame (Dano et al 2015), lupine (Jappe and Vieths 2010), mustard (Sirvent et al 2012), and celery (Fuchs et al 2012) have been identified as major allergenic food sources in European countries. Shellfish is the most common food allergen from Asia (Lee et al 2013;Shek et al 2010;Wu et al 2012) whilst egg and cow's milk allergies are most prevalent among young children and infants in Asia too (Chen et al 2011;Lee et al 2013;Wu et al 2012). Estimates for the total number of consumers affected by food allergies range from 1-2% adults and 5-8% children in westernized countries (Gupta et al 2011;Patel et al 2011;Tang and Hsiao 2016).…”
Section: Introductionmentioning
confidence: 99%